Effect of Different Immobilizing Methods on L- Asparaginase Activity for Monitoring Leukemia - Hadi Sajed Abd-Al-Abbas (Journal of Global Pharma Technology, 2017)
Purified L-asparagines from Portulacaoleracea L. plant was immobilized by three immobilizing methods (agar , agarose and gelatin ) ,the activity of immobilized enzyme was determined and compared with free enzyme ,where immobilizing efficiency of agar , agarose and gelatin techniques was ( 72 %,78 % and 70 % ) respectively, all immobilizing technique proved an significant activity increasing of enzyme in compaction of free enzyme, where agar and gelatin methods showed more stability of enzyme at alkaline PH (PH 9) , whereas only agarose method get the enzyme more heat stability than other immobilizing methods. there are significant elevation level of asparagine concentration in leukemic human blood samples than normal human blood samples , where reached to 〖10〗^(-4)-〖10〗^(-7)M of asparagine in normal human blood samples while it was 〖10〗^(-2)-〖10〗^(-3) M of asparagine in leukemic human blood samples.